Popular culture texts: Thinking outside the book and onto the screen - Borrello, María Florencia (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
As current generations of students are entering the classroom having had years of “screen time,” it is imperative to rethink and remake traditional teaching practices. The present paper thus aims to explore multimedia publishing and the possibilities it has to offer foreign language learners in the consumption and production of popular culture texts. As multimodal types of literary texts, podcasting, video publishing and live streaming prove pivotal in enabling students become engaged in global communication.